Middle-distance runners` middle-altitude training process management mode - Mosin, I. V.; Esaulov, M. N.; Mosina, I. N. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the middle-altitude training process management model for middle-distance runners with lactate tests. The model testing experiment was completed at sport base in Kislovodsk located 800-850m above the sea level, with the athletes tested prior to and in days 4-6-8-10-12-14 of the training cycle. The trainings were designed to include 8x500m low-intensity races (LIR) with 500m breaks; plus 3x200m LIR with 200m breaks; 5x1000m LIR with 1000m breaks; 3?400m LIR with 400m breaks; 3x2000m LIR with 1000 breaks; and 3x200m uphill jumps. The training days were alternated by rehabilitative cross-country races taking 30/ 50min in the morning/ evening, respectively. Sampled for the experiment were the 18-19 years old Class I and CMS skiers (n=12, including 7 males and 5 females), with the training process intensity customized to the individual fitness and training needs of the athletes. The sample was tested for lactate level and HR.